Research on Improving Online Purchase Intention of Poverty-Alleviation Agricultural Products in China: From the Perspective of Institution-Based Trust - Li, Guangming; Wu, Xianghua; Yuan, Chao (Frontiers in Psychology, 2022)
Poverty-alleviation by consumption is a powerful way to help the poor people get rid of poverty, which plays a significant role in China's rural revitalization. However, the achievement of poverty-alleviation by consumption mostly depends on government procurement, and the enthusiasm of consumers to participate is low, facing the severe challenge of poor sustainability. Studies have shown that helping the poor is the most common motivation for consumers to buy poverty-alleviation agricultural products (PAAP). However, with the negative events of helping the poor and farmers, such as "slow-moving grandpa" and "posing", consumers' trust in sellers has been seriously damaged. The psychological protection system for fear of being cheated hinders consumers' purchase intention. Based on this, this study believed that trust will be an important factor that affects consumers' purchase intention of PAAP. E-commerce platform is the most important channel for consumers to buy PAAP, and institution-based trust is the most important way to generate trust in e-commerce environment. Therefore, this paper studied the institutional mechanisms that affect consumers' trust in the sellers of PAAP, and discussed the influence of trust on the online purchase intention of PAAP. Data were obtained through questionnaire survey and tested empirically. The results showed that the effectiveness of user feedback mechanism, platform supervision mechanism, product traceability mechanism and product certification mechanism can enhance consumers' purchase intention by enhancing their trust. Individual trust tendency positively regulated the relationship between the effectiveness of institutional mechanisms and consumer trust. The research results had important reference significance for promoting sustainable development of poverty-alleviation by consumption and rural revitalization.